2006
DOI: 10.1002/ange.200600061
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerization on Gold Nanoparticles through Rolling Circle Amplification: Towards Novel Scaffolds for Three‐Dimensional Periodic Nanoassemblies

Abstract: Recent years have witnessed an explosion of interest in the use of DNA-nanoparticle bioconjugates for programmed nanostructures, 1D or 2D nanoparticle arrays, nanoelectronics, and biosensing and biodiagnostics. [1][2][3][4][5][6][7][8][9] DNA was chosen as a polymeric material in these studies owing mainly to the specificity of DNA base-pairing, the predictability of inter-or intramolecular interactions, its physicochemical stability, and mechanical rigidity. In addition, DNA can be manipulated and modified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(20 citation statements)
references
References 25 publications
0
17
0
3
Order By: Relevance
“…This is useful for reporting on the state of cell signalling under physiological or pathological conditions such as inflammation. The 49 mer PDGF sensor sequence used in this study is ~16 nm when fully stretched in a duplex format 47 , and is expected to adopt a three-dimensional, tertiary structure upon binding to PDGF, leading to a dynamic radius less than ~8 nm. At this scale, the aptamer sensors sense signalling molecules at or near the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…This is useful for reporting on the state of cell signalling under physiological or pathological conditions such as inflammation. The 49 mer PDGF sensor sequence used in this study is ~16 nm when fully stretched in a duplex format 47 , and is expected to adopt a three-dimensional, tertiary structure upon binding to PDGF, leading to a dynamic radius less than ~8 nm. At this scale, the aptamer sensors sense signalling molecules at or near the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…This process led to the formation of micrometer‐long 1D chains of AuNPs 40. In a different approach, Li et al fabricate satellite‐like plasmonic nanostructures by RCA 41. In this report, DNA oligonucleotides were tethered to AuNPs as the primer and a single‐stranded circular DNA was used as a template.…”
Section: Dna‐programmed Self‐assemblymentioning
confidence: 99%
“…[12] RCA-T and the matching primer, "RCA-P", were used to perform the RCA reaction as described previously. [13] The details of this reaction and subsequent color-development procedures are provided in the Supporting Information. We found that DiSC2(5) retained the blue color in the hybridization buffer (50 mm Tris-HCl (Tris = 2-amino-2-hydroxymethylpropane-1,3-diol), pH 7.5, and 100 mm NaCl; Figure 2 b, tube 1).…”
Section: Monsur Ali and Yingfu Li*mentioning
confidence: 99%